2017
DOI: 10.1016/j.celrep.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Rlim -Dependent and -Independent Pathways for X Chromosome Inactivation in Female ESCs

Abstract: SUMMARY During female mouse embryogenesis, two forms of X chromosome inactivation (XCI) ensure dosage compensation from sex chromosomes. Beginning at the four-cell stage, imprinted XCI (iXCI) exclusively silences the paternal X (Xp), and this pattern is maintained in extraembryonic cell types. Epiblast cells, which give rise to the embryo proper, reactivate the Xp (XCR) and undergo a random form of XCI (rXCI) around implantation. Both iXCI and rXCI is dependent on the long non-coding RNA Xist. The ubiquitin li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 32 publications
3
45
1
Order By: Relevance
“…Thus, we performed RNA-seq experiments on RNA isolated from total testis of 8 weeks-old animals, comparing global gene expression in cKO/Y Sox2-Cre and fl/Y male littermates. These experiments including library construction, sequencing and data processing were performed as previously described (Wang et al 2017). Consistent with findings that attribute both positive and negative functions of RLIM for gene transcription (Bach et al 1999;Gontan et al 2012), statistical analyses revealed 118 downregulated and 83 up-regulated genes (threshold P<0.05) in cKO/Y Sox2-Cre animals (Figs.…”
Section: Diminished Production and Functionality Of Rlim Ko Spermsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, we performed RNA-seq experiments on RNA isolated from total testis of 8 weeks-old animals, comparing global gene expression in cKO/Y Sox2-Cre and fl/Y male littermates. These experiments including library construction, sequencing and data processing were performed as previously described (Wang et al 2017). Consistent with findings that attribute both positive and negative functions of RLIM for gene transcription (Bach et al 1999;Gontan et al 2012), statistical analyses revealed 118 downregulated and 83 up-regulated genes (threshold P<0.05) in cKO/Y Sox2-Cre animals (Figs.…”
Section: Diminished Production and Functionality Of Rlim Ko Spermsupporting
confidence: 53%
“…RNA-seq on RNA isolated from testes of fl/Y and cKO/Y males including library construction and sequencing on a NextSeq 500 was carried out essentially as described (Wang et al 2016;Wang et al 2017). Reads (paired end 35 bp) were aligned to the mouse genome (mm10) using TopHat (version 2.0.12) (Trapnell et al 2009), with default setting except set parameter read-mismatches was set to 2, followed by running HTSeq (version 0.6.1p1) (Anders et al 2015), Bioconductor packages edgeR (version 3.10.0 ) (Robinson and Smyth 2007;Robinson et al 2010) and ChIPpeakAnno (version 3.2.0) (Zhu et al 2010; Zhu 2013) for transcriptome quantification, differential gene expression analysis, and annotation.…”
Section: Rna-seq and Data Analysesmentioning
confidence: 99%
“…For the present study, we generated Rnf12 CR−/CR− ESCs through complete removal of the open reading frame of Rnf12 , and compared these cells with Rnf12 −/− ESCs that we generated in a previous study, which express a 333 aa N-terminal peptide that does not contain the catalytic Ring finger domain. Both Rnf12 CR−/CR− ESCs and Rnf12 −/− ESCs display stabilization and nuclear localization of REX1, contrasting a recent report that suggested a role for this 333 aa N-terminal peptide in the nuclear localization of the stabilized REX1 27 . Our quantitative mass spectrometry analysis revealed REX1 to be the main target of RNF12.…”
Section: Discussioncontrasting
confidence: 89%
“…[ 67 ] Complete absence of Rnf12 by contrast prevents random XCI in differentiating mESCs and imprinted XCI in early mouse embryos, while random XCI in vivo has been reported to be unaffected. [ 69–71 ] The mESC phenotype, however, seems to depend on the precise culture conditions, [ 72 ] maybe because rapid downregulation of Rex1 under certain conditions might make XCI Rnf12‐independent. Interestingly, experiments with heterozygous Rnf12 mutants where the single intact copy of Rnf12 is silenced during XCI have shown that XCI cannot be maintained without an active Rnf12 allele.…”
Section: Candidate Regulators and Mechanismsmentioning
confidence: 99%